Integration of Traditional Game in Problem Based Learning To Improve Critical Thinking Skills of Junior High School Students - Winarni, Nasrunniati Dyahayu Anggi; Mulyati*, Yayuk; Hamimi, Erti (Universitas Syiah Kuala, 2025)
The 2015 TIMSS and 2018 PISA results show that Indonesia's science performance remains below the international average and declined further in 2022. This indicates students weak critical thinking skills (CTS) in understanding scientific concepts. An effective and interactive learning model is needed. This study aims to compare students' CTS using the traditional game in problem-based learning (TG-PBL) model and the problem-based learning (PBL) model. The research used a quasi-experimental design with a pretest-posttest non-equivalent control group and purposive sampling. Statistical tests included the paired sample t-test, independent sample t-test, and N-gain score. The independent t-test showed a significant difference between TG-PBL and PBL classes (0.000). The paired t-test showed a difference between pretest and posttest in both classes (0.000), with a greater increase in the TG-PBL class. The N-gain in the TG-PBL class was 0.57 (medium category), while in the PBL class it was 0.24 (low category). The highest improvement in the TG-PBL class was in the basic support indicator (0.630), while in the PBL class it was in strategies and tactics (0.398). The TG-PBL model is more effective in improving students CTS. It creates a more interactive, relevant, and innovative science learning environment in junior high schools